Introduction to communication studies - Fiske, John. (Routledge classics., 2011)
This revised edition of a now classic text includes a new introduction by Henry Jenkins, explaining 'Why Fiske Still Matters' for today's students, followed by a discussion between former Fiske students Ron Becker, Elana Levine, Darrell Newton and Pamela Wilson on the theme of 'Structuralism and Semiotics, Fiske-Style'. Both underline the continuing relevance of this foundational text in communication studies.